Dimensions Of Human Nature Between Machiavelli And Thomas Hobbes - HazhanMala Hamadameen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
In the midst of all the beings in the world, man is the only conscious being, possessing intelligence and questioning. That is why man, himself, owns a research project in himself and the world around him. Man is also the creator of history and at the same time records history. Among all living things, man is known as the one who makes every effort for his own survival. For this reason, human beings have a "selfish" and conflicting nature. In the aftermath of the Middle Ages and at the beginning of the Renaissance Revolution, and in the depths of this revolution, two great philosophers came to the realm of political philosophy. They were also (Machiavelli) and (Thomas Hobbes). They dedicate their philosophical foundations to the study and analysis of complex human phenomena. In their view, human beings are selfish, and therefore need to be tightly controlled or restricted by a strict system of governance. In this study, we will try to discuss the fundamentals and different theories of these two philosophies about human nature.